Manajemen Mutu Pendidika Di SMA Negeri 2 Tanjungbalai - Rahmat Hidayat, Willi, Novia (Pusdikra Publishing, 2021)
This study aims to obtain data in SMA Negeri 2 Tanjungbalai which aims to determine the quality of education quality management in SMA Negeri 2 Tanjungbalai. This research was conducted from October 2020 to December 2020. Researchers used a qualitative approach and descriptive methods. Data collection was carried out through observation, interviews, and documentation study. The sources of this research are: the principal, the vice principal, the teacher. Planning for education quality management at SMA Negeri 2 Tanjungbalai begins with planning based on the results of the previous program evaluation. Planning is approved at a meeting of principals and teachers at the beginning of the school year. The planning process is guided by customer needs, vision, mission, and school goals, as well as government regulations. The implementation of quality management education at SMA Negeri 2 Tanjungbalai involves every element in the school according to their respective capacities and parts. In carrying out the implementation of the school based on the agreed program, government regulations, as well as the quality objectives of SMA Negeri 2 Tanjungbalai according to the vision and mission Supervision of education quality management at SMA Negeri 2 Tanjungbalai uses several strategies to supervise, namely forming a direct supervision team in schools whose officers are senior teachers in collaboration with Counseling Guidance teachers and parents, as well as monitoring student council activitiemonitoring activity of OSIS